The Influence Of Green Accounting Implementation And Good Corporate Governance Mechanisms On The Profitability Of Manufacturing Companies Listed On The Indonesia Stock Exchange In 2019-2023 - Musemmil, Muhammad; Ningsih, Wiwik Fitria; Rakhmawati, Ratih (Majalah Ilmiah DIAN ILMU, 2024)
This research aims to analyze and prove the effect of implementing Green Accounting and Good Corporate Governance mechanisms which include managerial ownership, board of directors, independent board of commissioners and audit committee on profitability. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2019-2023. This research used a sampling technique, namely purposive sampling, so that a sample of 12 companies was obtained. The data analysis method uses multiple linear regression analysis with the help of IBM SPSS Statistics 25. The research results show that partially the managerial ownership and audit committee variables have no effect on profitability. Meanwhile, the variables Green Accounting, board of directors and independent board of commissioners influence profitability. Simultaneously, the variables Green Accounting, managerial ownership, board of directors, independent board of commissioners and audit committee influence profitability.